On the new - Groys, Boris (London Verso, 2014)
One of the most influential voices in contemporary cultural theory on how to make it newAs ideas move from one context to another, something new is created. This continuous shifting of the line that separates the valuable from the worthless, culture from profanity, is at the centre of Boris Groys's investigation.